Algebra 2 (1st Edition)

Published by McDougal Littell
ISBN 10: 0618595414
ISBN 13: 978-0-61859-541-9

Chapter 5 Polynomials and Polynomial Functions - 5.1 Use Properties of Exponents - 5.1 Exercises - Skill Practice - Page 334: 45



Work Step by Step

Here, we have $(a^5 b^4)^2=(a^5)^2 (b^4)^2$ Here, we have $(a^5)^2 = a^{10}$ and $(b^4)^2=b^8$ Now, $a^{10}b^{8}=a^{14} b^{-1}=e$ This gives; $e=\dfrac{a^{10}b^{8}}{a^{14} b^{-1}}=a^{10-14} b^{8-(-1)}$ Hence, $e=a^{-4}b^9$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.